Analysis of Parenting Patterns on The Progress of Self-Development of Children with Special Needs - Nurmalasari, Risa Aditiya; Kristiana, Dian; Irsad Rusdiani, Nurtina (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This reseach aims to determine the parenting patterns of parents who have children with special needs. This research uses a qualitative approach and is a case study type of research conducted at the Pesantren Anak Sholeh (PAS) Baitul Qur’an Kindergarten Ponorogo. Respondents were parents of students with several different types of learning barriers, and special accompanying teachers. Data collection is observation, interviews, and documentation. The data analysis technique was using reducting the data, displaying the data, and conclusion. The data validity and reability techniques were using source triangulation and method triangulation. Based on the results of the research conducted, the analysis of parental parenting pattern on the development of children’s self-development is: 1) the form of parenting for each child is different, parents who have children with hearing impairments and Down syndrome apply democratic parenting, while parents who have children with hyperactive disabilities apply authoritarian parenting. Meanwhile, parents who have children with speech delays apply a permissive parenting style. One important factor that differentiates these parenting style is that parents try to implement parenting pattern according to the type of obstacles and need of the child.